2003
DOI: 10.1124/jpet.103.051805
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in Vivo Lipopolysaccharide Infusion on Vasoconstrictor Function of Rat Isolated Mesentery, Kidney, and Aorta

Abstract: Continuous infusion of lipopolysaccharide (LPS) into conscious rats elicits regionally selective cardiovascular disturbances. The aim of the present study was to assess contractile function in different vascular preparations (renal, mesenteric, and thoracic aorta) taken from rats infused with LPS for 2 or 24 h. Sustained responses to continuous infusion of methoxamine but not to KCl were reduced in the aorta (at 2 and 24 h LPS) and mesentery (at 24 h LPS) but not in the renal vascular bed. In contrast, transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…There is little doubt that there are heterogeneous responses to vasoactive agents among organs and vascular beds. The renal circulation relative to others is commonly spared from the typical agonist hyporesponsiveness seen in endotoxemic conditions (34,35). Furthermore, in contrast to the impaired contraction of isolated aorta to ␣-adrenoceptor stimulation, contractions to a TxA 2 agonist were unaffected by LPS infusion (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little doubt that there are heterogeneous responses to vasoactive agents among organs and vascular beds. The renal circulation relative to others is commonly spared from the typical agonist hyporesponsiveness seen in endotoxemic conditions (34,35). Furthermore, in contrast to the impaired contraction of isolated aorta to ␣-adrenoceptor stimulation, contractions to a TxA 2 agonist were unaffected by LPS infusion (34).…”
Section: Discussionmentioning
confidence: 99%
“…The renal circulation relative to others is commonly spared from the typical agonist hyporesponsiveness seen in endotoxemic conditions (34,35). Furthermore, in contrast to the impaired contraction of isolated aorta to ␣-adrenoceptor stimulation, contractions to a TxA 2 agonist were unaffected by LPS infusion (34). Thus, it is reasonable to postulate that the absence of hypocontractility to TxA 2 seems central to the renal vasoconstriction and emphasizes the primary role of TP receptors on renal hemodynamics during sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has demonstrated that hypocontractility to methoxamine in blood vessels from 24-h endotoxemic rats is not due to a generalized inability of the vascular smooth muscle to contract and does not appear to involve abnormalities in Ca 2+ mobilization or entry (Farmer et al, 2003). However, it has been proposed that contractile dysfunction may be primarily due to the direct deleterious effect of sepsis on vascular smooth muscle contractile mechanics/ machinery, based on the observation that maximum force of contraction in response to both phenylephrine and KCl was lowered without any change in their sensitivities in the aorta from a rat model of 48-h sepsis resulting from a soft-tissue infection with E. coli and B. fragilis (Price et al, 1999).…”
Section: Vascular Hyporesponsiveness To Vasocontractile Stimulimentioning
confidence: 99%
“…The general finding during endotoxemia is vascular hyposensitivity and hyporesponsiveness to constrictor substances such as norepinephrine (NE) and angiotensin II (Ang II); a weak response also holds for endothelium-dependent vasodilators (6 -11). Mixed results have been reported concerning vascular effects of vasopressin (AVP) and thromboxane (TxA 2 ) (9,11). Three different mechanisms have been implicated in the failure of the vascular smooth muscle cells (VSMC) to relax or constrict appropriately and the mediation of sepsis-induced generalized vasodilation, hypotension, and hyporesponsiveness (12).…”
Section: T He Incidence Of Severe Sepsis Is Increasing In the Unitedmentioning
confidence: 99%